2021
DOI: 10.3390/pharmaceutics13122095
|View full text |Cite
|
Sign up to set email alerts
|

Development of Lipid-Based Gastroretentive Delivery System for Gentian Extract by Double Emulsion–Melt Dispersion Technique

Abstract: Gentian (Gentiana lutea L., Gentianaceae) root extract (GRE) is used for the treatment of gastrointestinal disorders. However, its bioactive potential is limited in conventional forms due to the low bioavailability and short elimination half-life of the dominant bioactive compound, gentiopicroside. The aim of study was to encapsulate GRE in the lipid-based gastroretentive delivery system that could provide high yield and encapsulation efficiency, as well as the biphasic release of gentiopicroside from the tabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…AASLM powders prepare from both beeswax (Figure 7: F3a, F3b, F9a, F9b) and cetyl alcohol (Figure 7: F6a, F6b, F12a, F12b) with poloxamer showed a non-spherical shape and agglomerated tiny plates. This finding was in agreement with previous studies which reported that the SLM powder produced by freeze-drying process had non-spherical and agglomerated morphology (Alihosseini et al, 2015;Mudrić et al, 2021;Owuor et al, 2017). Moreover, the lipid concentrations had no impact on the surface morphology of SLM (Rosita et al, 2022).…”
Section: Scanning Electron Microscope (Sem)supporting
confidence: 92%
“…AASLM powders prepare from both beeswax (Figure 7: F3a, F3b, F9a, F9b) and cetyl alcohol (Figure 7: F6a, F6b, F12a, F12b) with poloxamer showed a non-spherical shape and agglomerated tiny plates. This finding was in agreement with previous studies which reported that the SLM powder produced by freeze-drying process had non-spherical and agglomerated morphology (Alihosseini et al, 2015;Mudrić et al, 2021;Owuor et al, 2017). Moreover, the lipid concentrations had no impact on the surface morphology of SLM (Rosita et al, 2022).…”
Section: Scanning Electron Microscope (Sem)supporting
confidence: 92%